Land of Fire - O'Connell, Ryan. (2017)
Abstract: Land of Fire is an orchestral work comprised of three movements, each based on a different chant sung by Lola Kiepja and recorded by ethnologist Anne Chapman in 1966. Kiepja was the last true Indian of the Selk'nam people, the former inhabitants of the largest island of Tierra del Fuego. The use of these chants as melodic source material within a new harmonic/textural setting is meant to be laudatory rather than an appropriation — an empathetic reach backward through time via the creation of new artistic work. In a broad sense, the work is an invitation for reflection on the often- neglected or overlooked brutality of Western powers upon Latin America throughout history. Alternatively, the piece may be thought of as the composer's attempt at a musical realization of the emotions and complex mental state(s) of the singer at the time of each chant's original vocalization.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Music.; Advisors: Shawn Jaeger, and John McDonald.; Committee: Shawn Jaeger, John McDonald, and Frank Lehman.; Keyword: Music.